A new species of Nebalia (Crustacea: Phyllocarida: Leptostraca) from the Cape d’Aguilar Marine Reserve, Hong Kong - Lee, Christine N. W.; Bamber, Roger N. (Zootaxa, 2011)
A new species of leptostracan, Nebalia mortoni, is described from the waters of the Cape d’Aguilar Marine Reserve, Hong Kong. It is distinguished from previously described species in particular owing to the squared denticles on the posterior dorsal margins of the pleonites. The species has been collected using baited traps, and has been the subject of previous study of its behaviour and demography. Laboratory culture of immature males has revealed that passage to maturity involved a sudden and dramatic lengthening of the antennae within the space of a single moult. This is only the second description of nebaliacean species from Asia.